Eksistensi Gamelan Selonding di Desa Bungaya, Kecamatan Bebandem, Kabupaten Karangasem, Bali - Diah Paramitha Ganeshwari, Ni Putu; Suarsana, I Nyoman (Humanis; Vol 18 No 1 (2017), 2017)
Gamelan becomes one important part in a ceremony of Balinese Hindu community. This is not out of the presence of gamelan as part of the " Panca Nada" . One type of Balinese gamelan used in a religious ceremony is gamelan selonding . In some regions, it is very sacred gamelan , one of them is Bungaya Village, District Bebandem, Karangasem, Bali. This study will reveal the history, function, and meaning of gamelan selonding in Bungaya village. This study uses the functionalism theory that proposed by Robert K Merton and theory of interpretative symbolic by Clifford Geertz. The functionalism theory used to uncover the manifest function and latent functions of gamelan selonding , while the interpretive theory used to reveal the symbolic meanings in the gamelan selonding for Bungaya Village community. This qualitative study done by ethnography method . Gamelan selonding Bungaya consisting of ten (10) compositions. Selonding Bungaya is one of the largest selonding in Bali i.e. 92 pieces of blades with varying sizes. Gamelan selonding Bungaya very rarely sounded, just in the usaba gede ( usaba dangsil ) which held in ten years. However, since the 1990s, the orchestra is also sounded at the time of the ceremony maligia in Puri Karangasem. Technology development leads to some changes in people's views about the gamelan selonding Bungaya. In the past, was so sacred and people are not allowed to record gamelan selonding in any form. Some elder figure in Bungaya still retain the rule, but among young people today no longer considers the efforts of documentation as something wrong, it had a positive impact on conservation efforts. Nonetheless, the gamelan Selonding Bungaya agreed that in the village they are holy and sacred.
Keywords: gamelan Selonding, Ida Bhatara Bagus Selonding, sacred